A pedagogia no campo expandido da arte: a 8ª Bienal do Mercosul - Louzada, Marina Lanzoni [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This research intend to investigate the main concepts on the pedagogical activities from the 8th Bienal de Artes Visuais do Mercosul, through its history and in a field research made in 2011, by the occasion and in the same year of that edition. It tries to recognize the innovative points of its pedagogical curatorial project and its meaning for the educational art in museums - the expanded field of the art. The expository and educational experience in the Bienal do Mercosul, through its concepts, proposes a reflection about educational art in museums or big events

O objetivo desta pesquisa é investigar os conceitos norteadores das atividades pedagógicas da 8ª Bienal de Artes Visuais do Mercosul, através de uma passagem sobre sua história e uma pesquisa de campo realizada em 2011, na ocasião desta edição. Reconhecer os pontos inovadores de seu projeto curatorial pedagógico e o seu significado para a arte-educação e para a educação em museus - o campo expandido da arte. A experiência expositiva e educativa da Bienal do Mercosul, através de seus conceitos propõe uma reflexão sobre arte-educação em museus ou grande eventos
Keywords: Arte na educação; Pedagogia critica; Arte; Artes plasticas; Art in education